Risk of recurrent venous thromboembolism after discontinuation of vitamin K antagonist treatment: a nested case–control study. (7th June 2016) - Martinez, C.; Katholing, A.; Folkerts, K.; Cohen, A. T.
Abstract : Essentials Vitamin K antagonists (VKA) in venous thromboembolism (VTE) lower the risk of recurrences. 41 841 VKA‐treated VTE patients had 1242 recurrent VTEs on therapy or early after cessation. An increased risk of recurrence was found in the first 120 days after VKA cessation. Patient education for the early detection of recurrent VTE after VKA cessation is recommended. Summary: Background: The standard treatment for venous thromboembolism (VTE) and the prevention of recurrent VTE (rVTE) consists of anticoagulant therapy. The optimal duration of anticoagulation depends on the presence of risk factors for rVTE. Objectives: To estimate the risk of rVTE in association with time since discontinuation of vitamin K antagonist (VKA) treatment. Methods: From the UK Clinical Practice Research Datalink with linked information on hospitalization and cause of death, a cohort of patients with a first VTE receiving initial VKA treatment between 2001 and 2013 was formed. With a nested case–control approach, patients with incident rVTE (cases) were matched to patients with VTE but without rVTE (controls). Adjusted rate ratios (RRs) of rVTE associated with time since VKA discontinuation relative to current VKA use were estimated from conditional logistic regression. Results: The VTE cohort comprised 41 841 patients with 1242 rVTEs and 6205 matched controls. The RR of rVTE was increased within 60 days following VKA discontinuation (RR 2.23, 95% confidence interval [CI] 1.71–2.91) and within 61–120 days following VKA discontinuation (RR 1.49, 95% CI 1.08–2.05) relative to current VKA use. The increased RR corresponded to excess incidence rates of 6.72 (95% CI 3.90–10.06) rVTE cases per 100 person‐years within 60 days, and of 2.68 (95% CI 0.42–5.58) rVTE cases per 100 person‐years within 61–120 days after VKA discontinuation. Conclusions: VKA discontinuation results in a transient increased risk of rVTE, which peaks within 60 days and lasts for up to 120 days after VKA discontinuation. Specific patient education for increased vigilance for signs and symptoms of recurrences is recommended in this period.